Allatotropin-like peptide released by Malpighian tubules induces hindgut activity associated with diuresis in the Chagas disease vector Triatoma infestans (Klug) - Santini, María Soledad (2007)
Haematophagous insects incorporate a large amount of blood with each meal, producing a big quantity of urine in a few hours to eliminate the excess water and Na+. Malpighian tubules (MTs) have traditionally been seen as a system that responds to neuroendocrine stimulus. In a related paper, we demonstrated that MTs of Triatoma infestans produce an autonomous endocrine secretion of an allatotropin-like (AT-like) peptide. In the present study, we report a myostimulatory activity of AT at the level of the hindgut (HG), associated with endocrine mechanisms regulating post-prandial diuresis. Allatotropin induced an increase in frequency and intensity of peristaltic contractions at the level of the HG. The release of the HG content in MTs-HG in vitro preparations undergoing an osmotic shock occurred at different times, depending on the number of MTs present, and there was no release in treatments without MTs. The application of an AT-antiserum to MTs-HG preparations undergoing osmotic shock produced a delay or a long-term blockade of diuresis, depending on the antiserum dilution applied. Similar results were obtained when AT-antiserum was applied in vivo prior to blood intake, decreasing the volume of urine eliminated during the first 2 h. Our results allow us to assign a specific endocrine function to the AT-like peptide released by MTs that is linked to the elimination of urine after blood meals.